Aplikasi Augmented Reality Pembelajaran Huruf Hijaiyah dalam Bahasa Isyarat Arab dan Indonesia - Fajrin Nur Utami; Umniy Salamah (Ikatan Ahli Informatika Indonesia (IAII), 2019)
Nowadays still many deaf Moslem could not be able to recite the Quran this is caused by a few media access for them to learn the Quran. In order to make the deaf Moslem capable to recite and comprehend the messages from The Quran, so they need the Quran that has been translated into Sign Language. The purpose of this research is to introduce Hijaiyah Letter to deaf Moslems by using Augmented Reality Technology that can be operated by using Android Smartphone. The data collection methods carried out in this research were observation and interviews at Skh YKDW 02 Tangerang. Retrieval of research data using the experimental test application method. Experiments to obtain primary data in the form of test results based on predetermined parameters, namely light intensity, occlusion, and detection distance. In addition, library research was conducted to obtain secondary data that supports this research such as journals and books. This research refers to Luther-Sutopo's multimedia development method as a system model in building applications. The results of black box testing on the application to find out whether the software is made in accordance with the expected or not, can be concluded that testing the functionality of the buttons contained in the application runs as expected. And the assessment survey of this application shows 87% positive response from the respondents whic lead to the very good category. In conclusion, this application would be well accepted by the users.